The Influence of Leadership and Compensation on Employee Performance at the Tulungagung Tobacco Factory - Puspitasari, Mifta Dea; Kristanti, Desi; Triwidyati, Endang (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
The orientation of the scientific work that the researcher has compiled is none other than as a benchmark for the implications of leadership and compensation on the performance of Tulungagung tobacco factory employees. This research uses a quantitative explanatory method using purposive sampling on 35 respondents. Observation, interviews, questionnaires are data collection methods that researchers use. Validity test, reliability test, classical assumption test, multiple regression test, coefficient of determination test, and hypothesis test as analysis of the data the researcher obtained. (1) partial test results or t test of the leadership variable with a value of 0.024. Thus, the Leadership variable (X1) partially has implications for the performance of Tulungagung tobacco factory employees, because the significant value is X1 = 0.024 < 0.05. So the researcher can state that the first hypothesis is accepted. (2) partial test results (t test) of the Compensation variable (X2) have a significant t value of 0.001. From these results, the compensation variable partially has significant implications or influence on the performance of Tulungagung tobacco factory employees. Which is the value of X2 = 0.001 < 0.05. So in this research the second hypothesis is accepted. (3) simultaneous test results (f test), Leadership (X1) and Compensation (X2) simultaneously influence Employee Performance (Y). Based on the calculation results obtained, the calculated F is 12.425 which is greater than F table 3.29 and the sig value is 0.000 <0.05, so H0 is rejected and H1 is accepted, so it can be concluded that the leadership and compensation variables influence the performance of Tulungagung tobacco factory employees. Keywords: leadership, compensation and employee performance.